Kekuatan dan Kesulitan Remaja Disabilitas di Yayasan Pendidikan Anak Cacat (YPAC) Jakarta dan Surakarta - Lestari, Tri Riana; Adyas, Atikah; Rachmawati, Elsye; Ardesa, Yopi Harwinanda; Pasaribu, Ester Syeftty (Politeknik Kesehatan Tanjungkarang, 2018)
Children with disability face the barriers due to their incapacity and various obstacles from their society. How to cope with the barriers that came from themselves due to physical imperfection, emotional instability, and obstacles from the environment will affect to their mental health. The Medical assessment to find out the strengths and difficulties of teenagers are intended to take early intervention and an effort to improve the mental and personality development of teenagers with disabilities. This research was conducted to find out about the description of disabled adolescence’s characteristic profile on strength and weakness that related to adolescence mentality at school for the disabled. The cross-sectional study was conducted at YPAC Jakarta and Surakarta in the period of June-October 2017. This research was conducted with 100 respondents from YPAC, 20 people from Jakarta and 80 people from Surakarta. The qualification of the respondents were adolescences with a range of age 11-18 years old, adolescents with limb and or vision disability that capable to communicate, and agree to be respondents. The study results showed that there were 27% children whose 11-12 years old, 24% whose 13-14 years old, 28% whose 15-16 years old, 21% whose 17-18 years old. The respondents were males 58% and females 42%. This research has successfully explained that Most of the difficulty level of adolescents with disabilities found in YPAC Jakarta and Surakarta were normal level (79%), and most of the level of strength were also normal level (89%). Suggestions for all parties related to disability adolescents as an effort to maintain mental health and not late to intervene.